30 mCi exploratory scan for two-step dosimetric 131I therapy in differentiated thyroid cancer patients: A novel approach and case report - Wu, Di; Gomes-Lima, Cristiane; Kulkarni, Kanchan; Burman, Kenneth; Wartofsky, Leonard; Van Nostrand, Douglas (World Journal of Nuclear Medicine, 2020)
Differentiated thyroid cancer patients with significantly elevated or rapidly rising serum thyroglobulin (Tg) levels and negative diagnostic radioiodine scans (DxScan) often present a therapeutic dilemma in deciding whether or not to administer an 131I treatment. In this report, we describe a novel two-step approach of a 30 mCi 131I exploratory scan before a dosimetric 131I therapy to help “un-blind” the treating physician of the benefit/risk ratio of a further “blind”131I treatment. A 51-year-old man presented with rising Tg levels, a negative DxScan, and a history of widely metastatic follicular thyroid cancer. He had undergone total thyroidectomy, remnant ablation with 3.8 GBq (103.5 mCi) of 131I, Gammaknife®, and treatment with 12.1 GBq (326 mCi) of 131I for multiple metastases. However, at 19 months after the treatments, his Tg levels continued to rise, and scans demonstrated no evidence of radioiodine-avid metastatic disease. In anticipation of a “blind”131I treatment, the medical team and the patient opted for a 30 mCi exploratory scan. The total dosimetrically guided prescribed activity (DGPA) was decided based on the whole-body dosimetry. The patient was first given 30 mCi of 131I, and the exploratory scan was performed 22 h later, which demonstrated 131I uptake in the left lung, left humeral head, T10, and right proximal thigh muscle. Based on the positive exploratory scan, the remainder of the DGPA was administered within several hours after the scan. On the post-DGPA treatment scan performed at 5—7 days, the lesions seen on the ~ 22 h exploratory scan were confirmed, and an additional lesion was observed in the left kidney. The 30 mCi exploratory scan suggested the potential for a response in the radioiodine-avid lesions despite a negative diagnostic scan. This method allows 131I treatment to be administered to patients who may have a greater potential for a therapeutic response while avoiding unwarranted side effects in those patients with nonavid disease.
Keywords: 131I treatment; 30 mCi exploratory scan; differentiated thyroid cancer; dosimetry; negative diagnostic scan; positive thyroglobulin